Strengthening Policies for Education, Innovation, and Digitization Through Teacher Training: Evaluating ProFuturo’s Open Model in Ecuador - Hernández-Sellés, Núria; Massigoge-Galbis, Miguel (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2024)
Teacher training and a commitment to innovation in teaching are determining factors in the success of technology adoption processes. This article presents a study on the opportunities produced through the collaboration of the Ecuadorian Ministry of Education and the ProFuturo program, which arose during the COVID-19 pandemic. This collaboration resulted in the improvement of digital competency among teachers and pupils and in transference to educational practise. It also strengthened the existing limited capabilities for developing mass training programs for teachers in the country. The research was conducted through an online survey, with a cross-sectional, quantitative, and non-experimental focus from two data sources. A total of 3,565 teachers answered the digital survey for teachers trained using the Open Model in Ecuador between 2020 and 2022. On the other hand, 7,257 teachers answered the ProFuturo Self-Assessment of Digital Skills of Teachers (https://competencyassessment.profuturo.education/?lang=en). The results show an improvement in the competency of teachers following their participation in the program and confirm that they considered digital transformation in the classroom to be of great utility. Teacher training remains a cornerstone of high-quality education and research as this contribution proves a positive impact on learning experiences, where there was a significant transference, driven by an improvement in digital skills applied to the teaching process.